Identifying and mitigating the impacts on primates of transportation and service corridors. Issue 1 (23rd November 2021) - Galea, Benjamin; Humle, Tatyana
Abstract: Most primate populations are declining; 60% of species face extinction. The expansion of transportation and service corridors (T&S) (i.e., roads and railways and utility and service lines) poses a significant yet underappreciated threat. With the development of T&S corridors predicted to increase across primates' ranges, it is necessary to understand the current extent of its impacts on primates, the available options to mitigate these effectively, and recognize research and knowledge gaps. By employing a systematic search approach to identify literature that described the relationship between primates and T&S corridors, we extracted information from 327 studies published between 1980 and 2020. Our results revealed that 218 species and subspecies across 62 genera are affected, significantly more than the 92 listed by the IUCN Red List of Threatened Species. The majority of studies took place in Asia (45%), followed by mainland Africa (31%), the Neotropics (22%), and Madagascar (2%). Brazil, Indonesia, Equatorial Guinea, Vietnam, and Madagascar contained the greatest number of affected primate species. Asia featured the highest number of species affected by roads, electrical transmission lines, and pipelines and the only studies addressing the impact of rail and aerial tramways on primates. The impact of seismic lines only emerged in the literature from Africa and the Neotropics. Impacts are diverse and multifaceted, for example, animal–vehicle collisions, electrocutions, habitat loss and fragmentation, impeded movement and genetic exchange, behavioral changes, exposure to pollution, and mortality associated with hunting. Although several mitigation measures were recommended, only 41% of studies focused on their implementation, whereas only 29% evaluated their effectiveness. Finally, there was a clear bias in the species and regions benefiting from research on this topic. We recommend that government and conservation bodies recognize T&S corridors as a serious and mounting threat to primates and that further research in this area is encouraged. Abstract : Identificación y Mitigación de los Impactos de los Corredores de Transporte y Servicio sobre los Primates Resumen: La mayoría de las poblaciones de primates están declinando; el 60% de las especies enfrentan la extinción. La expansión de los corredores de transporte y servicios (T&S) (es decir, carreteras y ferrocarriles, así como líneas de servicio y utilidad) representa una amenaza significativa pero subestimada. Con el pronóstico de que el desarrollo de corredores T&S incrementará a lo largo de la distribución de los primates, es necesario entender hasta dónde llega actualmente su impacto sobre los primates, las opciones disponibles para mitigar estos impactos de manera efectiva y reconocer las brechas entre la investigación y el conocimiento. Mediante una estrategia de búsqueda sistemática para identificar la literatura que describe la relación entre los primates y los corredores T&S, extrajimos información de 327 estudios publicados entre 1980 y 2020. Nuestros resultados revelaron que 218 especies y subespecies de 62 géneros están siendo afectadas, una cifra significativamente mayor que las 92 especies publicadas en la Lista Roja de Especies Amenazadas de la UICN. La mayoría de los estudios fueron realizados en Asia (45%), seguida de África (31%), los Neotrópicos (22%) y Madagascar (2%). Brasil, Indonesia, Guinea Ecuatorial, Vietnam y Madagascar arrojaron el mayor número de especies de primates afectadas. Asia contó con el número más alto de especies afectadas por carreteras, líneas de transmisión eléctrica y tuberías, así como los únicos estudios que abordaron el impacto del ferrocarril y el tranvía aéreo sobre los primates. El impacto de las líneas sísmicas sólo emergió en la literatura proveniente de África y los Neotrópicos. Los impactos son diversos y multifacéticos; por ejemplo, colisiones entre animales y vehículos, electrocuciones, pérdida y fragmentación del hábitat, impedimento del movimiento y el intercambio genético, cambios etológicos, exposición a la contaminación y mortalidad asociada con la caza. Aunque varias medidas de mitigación aparecían como recomendaciones, sólo el 41% de los estudios se enfocó en su implementación, mientras que sólo el 29% evaluó su efectividad. Finalmente, fue evidente un sesgo hacia las especies y regiones beneficiadas por las investigaciones sobre este tema. Recomendamos que los órganos gubernamentales y de conservación reconozcan a los corredores T&S como una amenaza seria y creciente para los primates y promovemos que se realicen más investigaciones en esta área. 【摘要】: 大多数灵长类动物的数量都正在下降; 其中 60% 的物种面临灭绝。运输及服务通道 (即公路、铁路及公共设施和服务线路) 的扩张构成了一项重要的但未得到重视的威胁。随着运输及服务通道的发展, 它们预计会越来越多地出现在灵长类动物分布范围内, 因此有必要了解其对灵长类动物当前的影响程度和有效缓解这些影响的可用方案, 并认识到研究和知识的空缺。我们通过系统搜索的方法确定了描述灵长类动物和运输及服务通道之间关系的文献, 并从 1980–2020 年间发表的 327 项研究中提取了相关信息。结果显示, 灵长类动物中 62 个属的 218 个物种及亚种受到了影响, 明显多于《世界自然保护联盟濒危物种红色名录》中列出的 92 个物种。这些研究大多数位于亚洲 (45%), 其次是非洲大陆 (31%), 新热带地区 (22%) 和马达加斯加 (2%)。巴西、印度尼西亚、赤道几内亚、越南和马达加斯加受到影响的灵长类物种数量最多。亚洲受到公路、输电线路和管道影响的物种最多, 同时亚洲也是唯一有研究涉及铁路和空中缆车对灵长类动物影响的地区。只有非洲和新热带地区的文献报道了地震测线的影响。此外, 动物受到的影响是多样化和多方面的, 例如动物与车辆碰撞、触电、栖息地丧失和破碎化、动物移动和基因交流受到阻碍、行为改变、污染暴露以及与狩猎相关的死亡等。尽管研究推荐了一些减缓影响的措施, 但只有 41% 的研究关注这些措施的实施, 而只有 29% 的研究评估了其有效性。我们还发现, 该主题的研究在物种和地区方面存在明显的倾向性。我们建议政府和保护机构认识到运输及服务通道对灵长类动物造成了严重且日益增长的威胁, 并鼓励在这个领域进行进一步的研究。【翻译: 胡怡思; 审校: 聂永刚】